2020
DOI: 10.1088/1742-6596/1594/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mobile Learning Media on Computer Assembly at Vocational High School

Abstract: The purpose of this study was to determine the effectiveness of mobile learning media in computer assembly subjects in vocational high schools. Previously this media had been declared valid by media experts and material experts, which was then used by students. The research method used in this study is quasi-experimental, with time-series research design. Data collection techniques with pretest and posttest. The effectiveness obtained from the results of the post-test seen from classical completeness, all stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Descriptive and inferential statistical analysis has demonstrated the significant effect of the AGRONUTRI-X M-learning apps on academic achievement in the topic of fertigation nutrients mix. Previous research studies conducted by Klimova (2019); Prasasti et al (2019); Sukardi et al (2020) have similarly demonstrated the efficacy of utilising M-learning as an educational resource. Numerous studies have demonstrated that the utilisation of M-learning apps has effectively brought positive results in the context of academic achievement and student performance within their respective fields of study.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 81%
“…Descriptive and inferential statistical analysis has demonstrated the significant effect of the AGRONUTRI-X M-learning apps on academic achievement in the topic of fertigation nutrients mix. Previous research studies conducted by Klimova (2019); Prasasti et al (2019); Sukardi et al (2020) have similarly demonstrated the efficacy of utilising M-learning as an educational resource. Numerous studies have demonstrated that the utilisation of M-learning apps has effectively brought positive results in the context of academic achievement and student performance within their respective fields of study.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 81%
“…Previous research findings also state that learning media is used as a learning tool in schools to improve the quality of education (Ahmad et al, 2021;Silaban & Rizal, 2020). Other findings also state that the media improves the quality of learning (Lidiana et al, 2018;Sukardi et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…Previous research findings also state that many students still lack learning resources (Artati et al, 2016;Simanihuruk & Simanungkalit, 2019). Other findings also state that the lack of learning resources or media will impact students' lack of motivation to learn (Hartini et al, 2017;Sukardi et al, 2020). Based on the prelimenary observation conducted in SD Negeri 7 Kubutambahan, the teachers were still fixated on the use of monoton text books provided by the government.…”
Section: Introductionmentioning
confidence: 97%
“…The conduct of this education focuses on creating a fun and enjoyable learning atmosphere through the provision of various learning activities to enhance the students creativity, attitude, and comprehension (Coyne et al, 2018;Ferri et al, 2020;Kandakatla et al, 2020). The teacher as the mentor and facilitator should be creative in integrating various learning sources and engging learning media (Hartini et al, 2017;Sukardi et al, 2020;Ula & Fadila, 2018). This instruction approach is precisely implemented to the elementary school education because the elementary students sit on the phase called golden period in which their potentials are quickly depeloved (Mustofa & Syafi'ah, 2018;Nur Jannah, 2020).…”
Section: Introductionmentioning
confidence: 99%